Left amygdala alterations mediate the effects of negative symptoms on social dysfunction in schizophrenia - Jin Fang; Yunshan Hu; Yan Li; Chaoran Wu; Yiding Lv; Xiaowei Tang; Xinyu Fang; Xiangrong Zhang; Chao Zhou (Schizophrenia)
Abstract Social dysfunction remains a core feature of schizophrenia (SCZ), particularly in individuals exhibiting prominent negative symptoms. The amygdala (AMYG), a key structure in emotional and social processing, may contribute to this dysfunction. This study investigated whether structural and functional alterations in the AMYG mediate the effects of negative symptoms on social functioning in SCZ. A total of 205 male participants were included: 53 with deficit schizophrenia (DS), 76 with non-deficit schizophrenia (NDS), and 76 matched healthy controls (HCs). Negative symptoms were assessed using the Scale for the Assessment of Negative Symptoms, and social functioning was evaluated with the Scale of Social Function in Psychosis Inpatients. Structural and resting-state functional MRI data were acquired. Amygdala volumes and region-of-interest-based functional connectivity (FC) were analyzed, and path analysis was used to test mediation effects. Patients with SCZ showed significantly reduced bilateral AMYG volumes compared to HCs. Within the SCZ group, the left amygdala (AMYG.L) was smaller than the right, with further reduction observed in DS compared to NDS. FC between the AMYG.L and the left superior temporal gyrus (STG.L) was also decreased in DS. Mediation analysis revealed that both AMYG.L volume and its FC with STG.L partially mediated the association between negative symptoms and poor social function. These findings suggest that AMYG.L abnormalities may involve social dysfunction in DS, offering potential targets for early intervention aimed at improving social outcomes in male patients with schizophrenia.